Does the use of a web-based collaborative platform reduce cognitive load and influence project-based student engagement? - Oluwajana, Dokun; Adeshola, Ibrahim; Clement, Seyefar (Springer, 2023)
The web-based supported collaborative learning is increasingly used to support student social activities in higher institutions. However, little is known about the factors of collaborative learning in a web-based supported learning environment. Therefore, this study examines the use of a web-based supported collaborative platform to enhance project-based student engagement. This research aims to determine the factors that determine collaborative learning and subsequent student satisfaction. Moreover, this research determines students' cognitive load understanding, social influence, and learner's motivation towards collaborative learning and the resultant impact of the web-based supported collaborative platform on student satisfaction. The data was collected from university post-graduate students who used the TRELLO platform. A total of 115 post-graduate students participated in this study, and the resulting data were analyzed based on partial least squares structural equation modelling statistical approach. The study results suggest that students' social influence and motivation positively influence collaborative learning; directly and indirectly, students are satisfied using a web-based supported collaborative learning platform to support project-based student engagement.
Keywords: Collaborative learning; Web-based learning; Cognitive load; Engagement; Social influence